Analysis Project Management on Cv. Nbw. Id by Cpm Method (Critical Path Method) - Ahmad, Hikmad Tullah; Safrizal; Dewi Rosa Indah (Jurnal Sinar Manajemen, 2024)
Project implementation can be successful when existing resources are used effectively and efficiently. One attempt to use the critical path (CPM) method is a project scheduling method that uses project planning analysis and fixed tim e estimates for each activity. In other words, this method can help solve the scheduling problem by determining the timing of the longest production process schedules in the project so that the company can effectively and efficiently determine how long a project can be completed. Optimization must be done to restore the project duration to the actual schedule. The data processing results are performed to determine the project control methods applied by the CV. NBW. ID and obtain a comparison of completion time between scheduling using the CPM (Critical Path Method) method and actual CV results. NBA. ID. To shorten the life of the project, it can be used CPM. The result of using the program on the project with the CPM method is that the project may be completed with a duration of 108 hours or approximately 13 days for one project at a cost of Rs 2.255.903,00 with a time difference of 18 hours.